The Issues of Unemployment in the Three Main Districts in the State of Perak Darul Ridzuan: Case Studies of Kinta, Manjung and Kuala Kangsar - Mariana Mohamed Osman; Syahriah Bachok (Journal of Architecture, Planning and Construction Management, 2020)
Unemployment is a problem which will affect various situations both social and economic development of a nation. Unemployment is one of the macroeconomic problems that signal the inefficient use of capital resource in the market. It is a stress condition faced by the community especially the unemployed people which will result in self destruction and low self-esteem. The paper discussed on the unemployment issues in the Districts of Kinta, Manjung and Kuala Kangsar in the state of Perak. Kruppe et al. (2007), defined unemployed as a person searching for employment through various channel such as advertisement agencies, sending out resume, or placing or answering advertisements and capable to work. In addition, the person also considered as unemployed if they are waiting response from any work agencies (Bradbury, 2007). A survey of 203 respondents were conducted randomly to identify the current socio-economic condition and the issues faced by the unemployed person in the three district of Kinta, Manjung and Kuala Kangsar in Perak. The result of the survey indicated that 35% of respondents were female, aged between 21- 25 years old (36.4%) and unemployed for more than 6 months. In addition, majority of respondents (57.1%) used newspaper as the medium to search for jobs rather than online internet search and did not know about the existence of local employment agencies i.e. PEKA located in Ipoh (13.8%).